2008
DOI: 10.1002/eji.200838678
|View full text |Cite
|
Sign up to set email alerts
|

Arginines in the CDR of anti‐dsDNA autoantibodies facilitate cell internalization via electrostatic interactions

Abstract: Internalization of autoantibodies against double-stranded DNA (anti-dsDNA) is crucial to the pathogenesis of systemic lupus erythematosus. Anti-dsDNA may bind to cell-surface targets in order to facilitate the subsequent cell penetration of the anti-dsDNA. In this study, we observed that the 9D7 monoclonal anti-dsDNA autoantibody (9D7 mAb) penetrates into Jurkat cells via a novel alternative pathway. Endocytosis inhibitors or a lipid-raft inhibitor did not significantly change the penetration of 9D7 mAb into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 49 publications
0
56
0
2
Order By: Relevance
“…2C10 contains three positively charged arginines in the CDR3-VH region (Jang et al 1996;Im et al 2015). Other known autoAbs that have multiple arginines in the region as well as 2C10 IgG have cell-penetrating properties (Foster et al 1994;Song et al 2008;Im et al 2015). Cell-penetrating autoAbs might bind to the cell membrane, before being internalized and endocytosed into cells, via charge-charge interactions of positively charged amino acids in the CDR3s, with negatively charged sulfated polysaccharides or glycosaminoglycans, such as heparan sulfate, on the cell membrane (Faaber et al 1986;Song et al 2008;Im et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2C10 contains three positively charged arginines in the CDR3-VH region (Jang et al 1996;Im et al 2015). Other known autoAbs that have multiple arginines in the region as well as 2C10 IgG have cell-penetrating properties (Foster et al 1994;Song et al 2008;Im et al 2015). Cell-penetrating autoAbs might bind to the cell membrane, before being internalized and endocytosed into cells, via charge-charge interactions of positively charged amino acids in the CDR3s, with negatively charged sulfated polysaccharides or glycosaminoglycans, such as heparan sulfate, on the cell membrane (Faaber et al 1986;Song et al 2008;Im et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Other known autoAbs that have multiple arginines in the region as well as 2C10 IgG have cell-penetrating properties (Foster et al 1994;Song et al 2008;Im et al 2015). Cell-penetrating autoAbs might bind to the cell membrane, before being internalized and endocytosed into cells, via charge-charge interactions of positively charged amino acids in the CDR3s, with negatively charged sulfated polysaccharides or glycosaminoglycans, such as heparan sulfate, on the cell membrane (Faaber et al 1986;Song et al 2008;Im et al 2015). The observations that 2C10 variable light domain (VL), which has no arginine residues in the CDR3 region, and G5-8 IgG, which has only one arginine in CDR3-VH, did not bind to antigen and did not penetrate into MES cells (Jang and Stollar 1990;Jang et al 1998;Im et al 2015) also provide evidence for the critical role of multiple arginines in 2C10 IgG and VH domains in cellpenetration.…”
Section: Discussionmentioning
confidence: 99%
“…However penetration of cells by autoantibodies has been described for various intracellular antigens, including nuclear antigens RNP [176], Ro and La [177,178] and double-stranded DNA (dsDNA) [179][180][181][182][183], as well as ribosomal P proteins [184], the E2 subunit of the pyruvate dehydrogenase complex (PDC-E2) located in mitochondria [185], and neuronal and retinal proteins [186,187]. Such penetration has been associated with functional changes that may differ according to the phase of the cell cycle or state of activation of the particular cell [177,181,188].…”
Section: Pathogenic Effects Of Autoantibodies To Intracellular Antigensmentioning
confidence: 99%
“…Penetration and translocation were linked to increased lysines and arginines in the complementarity determining regions (CDR) of the antibodies, and peptides corresponding to CDR2 linked to CDR3 of several penetrating mAb were designed that penetrated cells, and could be used as a vector to transport macromolecules [180,196]. Further studies showed that this was associated with electrostatic interactions of arginine residues in the CDR interacting with negatively charged sulphated polysaccharides on the cell surface [183], and arginine-rich cell penetrating peptides are now being investigated as promising tools for precise intracellular drug delivery [197,198].…”
Section: Pathogenic Effects Of Autoantibodies To Intracellular Antigensmentioning
confidence: 99%
“…Nephritogenic action of ICs is mediated primarily by interaction with Fc receptors and Toll-like receptors, and, to a lesser extent, through classical pathway of complement activation [16]. In addition, autoantibodies could interfere in functioning of circulating, membrane, or even intracellular molecules [17].…”
Section: Introductionmentioning
confidence: 99%